Evaluation of Semi-Nested PCR Compared with Indirect-ELISA to Diagnose Human Fasciolosis - Gita Alizadeh; Mojgan Aryaeipour; Mehdi Mohebali; Gholam Reza Mowlavi; Vahid Raissi; Mohammad Bagher Rokni (Tehran University of Medical Sciences, 2022)
Background: We aimed to compare semi-nested PCR with indirect ELISA to diagnose human fasciolosis. Methods: Overall, 70 serum samples were collected from different areas in Iran suspected for fascioliasis. Individuals were classified based on diagnostic of fascioliasis and habitat in endemic areas. Finally, all serum samples were tested by indirect ELISA (using secretory excretory antigen) and semi-nested PCR (using ITS1 gene). The study was conducted in the School of Publish Health, Tehran University of Medical Sciences, Iran in 2021. Results: Significant differences were found between agreement and similarity of patients' results of indirect ELISA and semi-nested PCR 94.46% and 98.4% respectively (Cohen's kappa ≥0.6; P-value≤0.05). No cross-reactions were observed with other parasitic diseases (toxocariasis, hydatidosis, strongyloidiasis, toxoplasmosis, cutaneous leishmaniasis, taeniasis and trichinosis). 69.84% of samples were positive by both techniques. In addition, the percentage of agreement and similarity between the results of the two techniques based on habitat in endemic areas was 88.9-100% and 97.7-100%, respectively (Cohen's kappa ≥0.6; P-value≤0.05). Conclusion: Semi-nested PCR could be a suitable method for following up on patients' treatment and a confirmatory method for ELISA as for diagnosis of human fascioliasis.